Migrant Care : A Web-based Support System for Migrant Workers (Journal of Information Technology and Digital World, 2025)
Migrant Care aims to enhance support for Migrant workers in Tamil Nadu by developing a web-based platform to address challenges such as language barriers, limited real-time assistance, and inefficient administrative oversight. The proposed method involves developing a centralized system using Next.js for frontend, Convex for real-time backend services, and Firebase for secure authentication, enabling worker registration, complaint submission with immediate email notifications, and immediate announcements The research has integrated the i18n to resolve the language barrier, it supports six languages, such as Tamil, English, Telugu, Hindi, Kannada, and Malayalam. Migrant Care was designed for low literacy people and it has a simple and secure interface. The user-friendly web platform enables the migrants to easily sign up with their Email Id. Every migrant can have their own dashboard secured with their 12-digit unique ID . It enables the migrant to register with basic details, such as name, work, workplace, and contact. This platform with the details of the migrant can be used to file their complaints to the corresponding authority. The complaints reach the authority in form of high priority email alerts. The necessary announcements are updated by the administrator to keep every member in the platform informed about the important updates. Migrant Care has the special Admin Dashboard to monitor all the migrant data, complaints, and updating the announcements. Thus, the web platform was built to tackle the real struggles of the migrant workers.
Keywords: Migrant Care; Next.js; Convex; Firebase; Administrator; Announcement